The Role of Kyai, Santri, and Nasional (Abangan) in Political Identity Struggle: a Case Study - Mochammad Faiz Eko Sulistyo Budi (Yayasan Rumah Peneleh, 2022)
This study aims to explore the implications of the concept of Kyai, Santri, and Nasional (Abangan) in the political struggle of a village. By employing qualitative approach, specifically an ethnographic approach and a thorough analysis of social construction theory and concept of identity politics, the author found several results, including those related to identity manipulation in the socio-political context of the village. Such unavoidable condition is caused by the supporting system in the society. The power of identity becomes very highly-regarded by the society, especially for those who will run for elite positions in village political contestations. The results of the study show that the continuity of the Kyai, Santri, and Abangan role occurs through a process of internalization in the midst of social institutions, externalization by the community with symbolic messages as a code for sub-identity, as well as objectivication of intersubjective-structured lifeworld.